Analisis User Behaviour Penerapan LMS Moodle Mobile dengan Metode TAM pada UMSIDA - Ibrahim Ibrahim; Tri Lathif Mardi Suryanto; Eristya Maya Safitri (Universitas Bandar Lampung (UBL), 2022)
The Muhammadiyah University of Sidoarjo is one of the universities that implement an e-learning learning model using an LMS called Moodle UMSIDA. However, the adoption of the application is not free from such shortcomings as failing when trying to log in and others. This problem causes students to prefer to use other e-learning alternatives and makes the Moodle UMSIDA application less attractive. The purpose of this study is to analyze the factors that influence the acceptance of the Moodle UMSIDA application. Based on previous studies, it is evident that the Technology Acceptance Model (TAM) is a suitable measuring tool for conducting this research. In this study, the TAM model was adopted and modified based on the model developed by Said A Salloum. There are 385 response data from students obtained through online questionnaires and offline interviews, then analyzed using SEM-PLS. Based on the results obtained in this study, the variables of accessibility, computer self-efficacy, perceived enjoyment, user behavior, and perceived ease of use were significant to the acceptance of the Moodle UMSIDA application. The results of the research are considered for the application manager in carrying out development.